Evaluation of foreign body aspiration cases in our pediatric intensive care unit: Single-center experience - Aslan, Nagehan (Turk Pediatri Ars, 2019)
AIM: Foreign body aspiration is one of the common home accidents that requires urgent diagnosis and treatment, especially in children aged between 1 and 3 years. The type, location, and obstruction level of the aspirated material, age of the patient, and time of diagnosis influence the severity of the clinical picture. In our study, we aimed to evaluate patients who underwent bronchoscopy in our clinic with a diagnosis of foreign body aspiration in light of literature data. MATERIAL AND METHODS: The medical records of 87 patients who underwent rigid bronchoscopy with a prediagnosis of foreign body aspiration in Çukurova University, Faculty of Medicine, between January 2016 and August 2018, and were followed up in the pediatric intensive care unit after the procedure were examined retrospectively. The subjects were evaluated in terms of age, sex, primary referal center, time of presentation, symptoms at presentation, physical examination findings, radiologic investigations, type and location of foreign body, and duration of stay in the intensive care unit. RESULTS: A total of 87 patients were included in the study. Thirty-seven patients (42.5%) were female. The mean age was found as 33.73±39.44 (range, 5–202) months. The most common (74.7%) symptom at presentation was sudden onset of coughing. The foreign body aspirated was organic in 62.1% of patients. The most common foreign bodies aspirated were peanuts, with a rate of 19.5%. Four adolescent female patients underwent broncoscopy because they aspirated needles they held in their mouths while tying their headscarves. Interestingly, one patient aspirated a stone and one patient aspirated a parasite. The most frequent location of foreign body was the right main bronchus (n=27, 31%). CONCLUSION: In the diagnosis of foreign body aspiration, the most important step is maintaining a high index of suspicion. Foreign body aspiration should be considered in patients who present with cough, respiratory distress or cyanosis, unilaterally diminished breath sounds, ronchi or stridor on physical examination, and air trapping on chest X-ray. Bronchoscopy is life-saving in the presence of any suspicious history suggestive foreign body aspiration or refractory pneumonia, even if a physical examination and radiologic findings are normal, especially in high-risk children between 1–3 years old.